Acquisition of New DNA Sequences After Infection of Chicken Cells with Avian Myeloblastosis Virus - Shoyab, M. (1974)
DNA-RNA hybridization studies between 70S RNA from avian myeloblastosis virus (AMV) and an excess of DNA from (i) AMV-induced leukemic chicken myeloblasts or (ii) a mixture of normal and of congenitally infected K-137 chicken embryos producing avian leukosis viruses revealed the presence of fast- and slow-hybridizing virus-specific DNA sequences. However, the leukemic cells contained twice the level of AMV-specific DNA sequences observed in normal chicken embryonic cells. The fast-reacting sequences were two to three times more numerous in leukemic DNA than in DNA from the mixed embryos. The slow-reacting sequences had a reiteration frequency of approximately 9 and 6, in the two respective systems. Both the fast- and the slow-reacting DNA sequences in leukemic cells exhibited a higher T(m) (2 C) than the respective DNA sequences in normal cells. In normal and leukemic cells the slow hybrid sequences appeared to have a T(m) which was 2 C higher than that of the fast hybrid sequences. Individual non-virus-producing chicken embryos, either group-specific antigen positive or negative, contained 40 to 100 copies of the fast sequences and 2 to 6 copies of the slowly hybridizing sequences per cell genome. Normal rat cells did not contain DNA that hybridized with AMV RNA, whereas non-virus-producing rat cells transformed by B-77 avian sarcoma virus contained only the slowly reacting sequences. The results demonstrate that leukemic cells transformed by AMV contain new AMV-specific DNA sequences which were not present before infection.